LiGaSe2 optical parametric oscillator pumped by a Q-switched Nd:YAG laser - Zondy, Jean-Jacques; Vedenyapin, V.; Boyko, A.; Kolker, Dmitri; Isaenko, L.; Lobanov, S.; Kostyukova, N.; Yelisseyev, A.; Petrov, V. (Laser Physics Letters, 2016)
Optical parametric oscillation is demonstrated for the first time with the chalcogenide nonlinear crystal LiGaSe2 pumped by a nanosecond Nd:YAG laser. Angle tuning provides coverage of the 4.8–9.9 μm spectral range in the mid-IR by idler pulses.
Keywords: optical parametric oscillator; mid-infrared; lithium gallium selenide